Remote Sensing with Internet Based Patient Condition Observing System - Pratibhahanmantrao Gaikwad; Dhiren Pranshankar Dave (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This Paper aims to design and demonstrate an innovative web-based remote healthcare diagnostic system that provides vital medical data and live video images of a patient situated in the rural area accessible to a health professional available elsewhere in urban centres resulting in better diagnosis and treatment of that patient.